Responsible lending as means of protecting consumers in credit contracts in the law of тhe European Union - Dudaš, Atila (Zbornik radova Pravnog fakulteta u Novom Sadu, 2020)
The traditional concept of consumer law relies on the so-called information paradigm. It postulates the ability of consumers to make rational choices if they are provided with all the necessary information as well as the required level of transparency of the transaction they are to enter into. The information paradigm gains special significance in consumer credit contracts. The reasons are manifold. Firstly, credit contracts are usually concluded for longer periods of time, quite often as long as a decade or two, in the cases of mortgage credit contracts. Secondly, they regularly involve higher financial commitment of the consumer than sale contracts the object of which is usually of lesser value in comparison to the value of credit contracts. Finally, the average consumer does not usually possesses the expertise and experience required to make rational decisions concerning the terms of a credit contract. Therefore the gap between the expertise and experience of the consumer and that of the creditor is a common occurrence. Due to the mentioned features of consumer credit contracts, the precontractual duties of the creditor are more extensive than that of the seller’s in a consumer sale contract. One of them is the creditor’s duty to grant credit to the consumer according to the concept of responsible lending. It requires the creditor to assess thoroughly and impartially the creditworthiness of the consumer before the conclusion of the contract, in order to prevent their over-indebtedness by avoiding credit contracts that are unreasonable from the perspective of the consumer. At the level of the European Union, consumer credit was first regulated by the Directive 87/102/ЕЕC. However, responsible lending as a special precontractual duty of the creditor has not appeared in this Directive yet. During the preliminary works on the new Directive 2008/48/EC on consumer credits one of the most debated issues was whether it should envisage explicitly responsible lending as one of the precontractual duties of the creditor. The first proposal of the new Directive contained a quite strict rule, presuming that the creditor assessed by all means available whether it could be reasonably expected that the consumer will be able to repay the credit, on the one hand, and that the creditor advised the consumer accordingly before the contract is concluded, on the other. Much of this rule was omitted from the final text of the Directive, though it still prescribes the duty of the creditor to assess the creditworthiness of the consumer. The financial crisis, which erupted in 2007, demonstrated how vulnerable the financial situation of the consumers may become and how fragile the system of collaterals supporting credit contracts may prove in time. The experience gained from the crisis was taken into account during the drafting of the new Directive 2014/17/EU, known in short as the Mortgage Credit Directive, which attaches a much greater importance to the concept of responsible lending.